Pengajaran Bahasa Arab melalui Metode Card Sort untuk Meningkatkan Maharatul Kitabah dan Qira’ah Siswa Kelas VIII MTs Al-Mukhtariyah Padang Lawas - Deni Hariansah; Harun al Rasyid (LPPM Institut Nasional Laa Roiba Bogor, 2024)
The most basic skills in learning Arabic are the skills of maharatul kitabah and maharatul qira'ah. These two skills greatly support students' skills and shrewdness to learn Arabic in class. Therefore, an appropriate Arabic learning method is needed to help students to improve the skills of maharatul kitabah and qira'ah, namely the card sort method. This study is a quasi-experimental study because researchers determine two classes that will be used as experimental classes and control classes randomly. The sample of this study was 30 students of grade VIII-1 as an experimental class and 30 students of grade VIII-2 as a control class. Based on the results of the study that the results of the first t-test were obtained t count ≥ t table which is 2.047 ≥ 2.01 and significance value is 0.045 < 0.05 so it is concluded that there is an average difference in the skills of maharatul kitabah in the experimental class and the control class. Through the results of the second t-test, t was obtained to calculate the ≥ t table, which was 2.481≥ 2.01 and the significance value was 0.016 < 0.05 so that it was concluded that there was an average difference in the skills of maharatul qira'ah in the experimental class and the control class. Through the manova results, it is obtained that the F value of the table ≥ F is 3.935 ≥ 3.15 and the significance value is 0.025 < 0.05 so that it can be said that there is a significant difference in average value. So it was concluded that teaching Arabic through the card sort method can improve the ability of maharatul kitabah and maharatul qira'ah students of grade VIII MTs Al-Mukhtariyah Padang Lawas. Keywords: Card Sort Method, Maharatul Kitabah, Maharatul Qira'ah